Effects of home prothrombin international ratio (PT-INR) management in children with mechanical prosthetic valves – Importance of individual correlations between laboratory and CoaguChek device PT-INRs. Issue 2 (February 2018) - Ino, Naomi; Masutani, Satoshi; Tanikawa, Shoyo; Iwamoto, Yoichi; Saiki, Hirofumi; Ishido, Hirotaka; Tamura, Masanori; Senzaki, Hideaki
Highlights: CoaguChek home monitoring reduced the number of outpatient clinic visits. No major clinical events were encountered during the study period of CoaguChek home monitoring. Individual correlation between CoaguChek and laboratory PT-INR needs to be identified. Abstract: Background: Warfarin administration is essential but requires difficult management and frequent clinic visits in patients with mechanical prosthetic atrioventricular valve replacement (MPAVVR). This study investigated how home prothrombin international ratio (PT-INR) monitoring with CoaguChek ® (Roche Diagnostics, Basel, Switzerland) safely reduced clinic visits in children with MPAVVR. We also compared individual correlations between the CoaguChek and laboratory PT-INR. Methods: This study included four pediatric patients who started frequent warfarin home-monitoring after MPAVVR (three mitral valves and one tricuspid valve). We collected information regarding the number of outpatient clinic visits and measurements of PT-INR before and after starting home CoaguChek monitoring (each one year) from medical records. We also compared individual correlations between laboratory and CoaguChek PT-INR in three patients. Results: No major clinical events were encountered during the study period. The ratio of outpatient clinic visits in the second year to those in the first year was decreased in all patients (0.30–0.66). The ratio of the numbers of home measurements to all PT-INR measurements in the second year ranged from 0.55 to 0.64 indicating that CoaguChek home monitoring approximately halved the number of outpatient clinic visits. CoaguChek measurements tended to be slightly overestimated in two patients but were greatly underestimated in one patient. Conclusions: CoaguChek home monitoring in children with MPAVVR reduced the number of their clinic visits without compromising the safety of warfarin management. Given considerable individual differences in correlations between CoaguChek and laboratory PT-INR, individual correlation needs to be identified to fairly interpret the CoaguChek PT-INR values.